Altered Expression of MicroRNAs in Rheumatoid Arthritis. Issue 1 (11th July 2017) - Tavasolian, Fataneh; Abdollahi, Elham; Rezaei, Ramin; Momtazi‐borojeni, Amir Abbas; Henrotin, Yves; Sahebkar, Amirhossein
ABSTRACT: Rheumatoid arthritis is one of the most common types of inflammatory joint diseases. Women, smokers, and people with positive family history are more susceptible to this disease. Diagnostic criteria include at least one swollen joint that has not been caused by other diseases. MicroRNAs are non‐coding RNAs that are evolutionarily conserved and have a length of 18–25 nucleotides. MicroRNAs control gene expression at the post‐transcriptional level via promoting mRNA degradation or translational repression. Recognition of alterations in microRNA status and their respective targets, may offer an opportunity to better identify the pathways that are involved in the etiopathogenesis of autoimmune diseases. It has been suggested that microRNAs may serve as potential biomarkers for both diagnosis and prognosis of autoimmune diseases. Here, we review the available evidence on the deregulations of microRNA expression in rheumatoid arthritis. More precisely, this review focuses on the microRNA involved in T cell regulation and gives perspectives on the use of this microRNA as biomarkers of diagnosis, prognosis, or intervention efficacy. J. Cell. Biochem. 119: 478–487, 2018. © 2017 Wiley Periodicals, Inc. Abstract : It has been suggested that microRNAs may serve as potential biomarkers for both diagnosis and prognosis of autoimmune diseases. Here, we review the available evidence on the deregulations of microRNA expression in rheumatoid arthritis.